Comparativo de veintiséis híbridos de maíz amarillo duro (Zea mays l.) con fines forrajeros en LAREDO, TRUJILLO - Castope Rodríguez, Adán Orlando (2014)
The present experimental work called "Comparative twenty six hard yellow maize hybrids (Zea mays L.) for forage purposes in Laredo, Trujillo" was installed in the town center of Santo Domingo in April 2013, it was used 22 experimental hybrids, 3 sales and 1 record from the cooperative program corn Universidad Nacional Agraria La Molina and marketer Pro Semillas S.A.C, the objectives in this research were to measure and compare the forage characteristics of twenty hybrids, identifying developmental stages and determine the experimental hybrids with greater forage potential. Conducting the experiment was conducted in a commercial field, under a system of surface irrigation in a sandy loam soil, poor in organic matter, rich in phosphorus available and medium available potassium, pH slightly acid 6.1, electrical conductivity acceptable 0.4 dS.m-1 and a dose of NPK 260-100-50. Statistical complete randomized design of 26 treatments with 4 replications was used, the population of the experiment was 71000 plants.ha-1, and each experimental plot consisted of 2 rows of 5.6 m. in length. The harvest took place on August 8, 2013. Performance characteristics (green and dry matter), phenological, morphological (plant height and stem diameter) and reproductive (male and female flowering), plus a nutritional chemical analysis of commercial hybrids was performed and the experimental reaching was recorded higher yield of fresh matter. We conclude that hybrid showed precocity, and the difference in the periods of emergence and flowering are the most influential in the crop cycle, the commercial hybrid Gran Dorado showed earlier age at reproductive stage R3 97 days and the other hybrids found in a range from 105 to 116 days.Hybrids showed statistically fresh matter yield equal to an average of 62.3 t ha-1 and different dry matter yield, the experimental and PM-213 with an average of 14.2 t ha-1 of dry matter were superior to PM-212 and Gran Dorado; experimental hybrid averaging 3.03 m. plant height were above the PM-213, PM-212 and Gran Dorado scored 2.67, 2.64 and 2.11 m. respectively; regarding hybrid stem diameter 2.0 cm on average obtained being statistically equal; likewise all hybrids flourished time with 73 days in male flowering and 76 days in the female, except that proved Gran Dorado earlier to 65.5 days in male flowering and 66 days in the women and finally the hybrids showed better foraging behavior in relation to dry matter yield were the experimental hybrids and the PM-213 commercial